Unpublished clinical studies in pediatric emergence delirium: a cross sectional analysis - Meyburg, Jochen; Ries, Markus (medRxiv, 2020)
Objectives Emergence delirium (ED) is a frequent and potentially serious complication of general anesthesia in children. Although there are various treatment strategies, no general management recommendations can be made. Selective reporting of study results may impair clinical decision making. We therefore analyzed whether the results of completed registered clinical studies in patients with pediatric ED are publically available or remain unpublished. - Design Cross sectional analysis. - Setting ClinicalTrials.gov and ClinicalTrialsRegister.eu - Participants and outcome measures We determined the proportion of published and unpublished studies registered at ClinicalTrials.gov and ClinicalTrialsRegister.eu that were marked as completed by September 1st 2018. The major trial and literature databases were used to search for publications. In addition, the study investigators were contacted directly. - Results Of the 44 registered studies on pediatric ED, only 24 (54%) have been published by September 2019. Published trials contained data from n=2556 patients, whereas n=1644 patients were enrolled in unpublished trials. Median time to publication was 19 months. Studies completed in recent years were published faster, but still only 9 of 25 trials were published within 12 months after completion. - Conclusion There is a distinct publication gap in clinical research in pediatric ED that may have an impact on meta-analyses and clinical practice. - Strengths and limitations of this studyThis study quantitates the amount of research waste in pediatric emergence delirium assessed as a) the number and b) sample sizes of published and unpublished completed clinical studiesThe precise reasons for non-publication of the studies included in this analysis remain unknownStrengths of findings as well as directions of individual unpublished studies remain unknownStudy registers other than ClinicalTrials.gov and ClinicalTrialsRegister.eu were not analyzed - Funding statement This research received no specific grant from any funding agency in the public, commercial or not-for-profit sectors.